Self-Efficacy: Fostering Student Creativity in Problem-Solving in Elementary Schools - Ike Yuli Mestika Dewi; Mochamad Nursalim; Diana Rahmasari (STAI Hubbulwathan Duri, 2025)
Problem-solving is a critical 21st-century skill that should be nurtured from an early age. However, elementary students often face challenges in mathematical problem-solving due to low self-efficacy, which can hinder their creativity and cognitive engagement. This study investigates the relationship between self-efficacy and mathematical problem-solving ability in elementary school students. A quantitative approach was employed using a quasi-experimental design with a nonequivalent control group. The sample consisted of 60 fourth-grade students from SDN Nurul Bayan, randomly assigned to experimental and control groups. Data were collected using a 35-item self-efficacy questionnaire and a mathematical problem-solving test comprising 9 descriptive items. Prior to hypothesis testing, the instruments underwent validity, reliability, normality, and homogeneity testing. Statistical analysis revealed a significant positive correlation between self-efficacy and mathematical problem-solving ability. The Pearson correlation coefficient was r = 0.553, with a p-value = 0.001, indicating a moderate and statistically significant relationship. These findings align with Bandura’s theory of self-efficacy, emphasizing its critical role in academic achievement. Enhancing self-efficacy appears to support the development of students' creative and analytical thinking in mathematical contexts. The study highlights the importance of incorporating psychological factors into mathematics instruction and suggests that pedagogical strategies should actively promote student confidence from an early stage.